Making a Difference: Bridging the Gap Between the Ivory Tower and the Community - Dan Rascher (Journal of Applied Sports Management, 2019)
Keynote address given at the 2019 ASMA Conference as part of the Lifetime Achievement Award ceremony.
Keywords: ASMA